Clinical Validation of the Analysis of Fluconazole in Oral Fluid in Hospitalized Children - van der Elst, Kim C. M. (Antimicrob Agents Chemother, 2014)
Fluconazole is a first-line antifungal agent for the treatment and prophylaxis of invasive candidiasis in pediatric patients. Pediatric patients are at risk of suboptimal drug exposure, due to developmental changes in gastrointestinal and renal function, metabolic capacity, and volume of distribution. Therapeutic drug monitoring (TDM) can therefore be useful to prevent underexposure of fluconazole in children and infants. Children, however, often fear needles and can have difficult vascular access. The purpose of this study was to develop and clinically validate a method of analysis to determine fluconazole in oral fluid in pediatric patients. Twenty-one paired serum and oral fluid samples were obtained from 19 patients and were analyzed using a validated liquid chromatography-tandem mass spectrometry (LC–MS-MS) method after cross-validation between serum and oral fluid. The results were within accepted ranges for accuracy and precision, and samples were stable at room temperature for at least 17 days. A Pearson correlation test for the fluconazole concentrations in serum and oral fluid showed a correlation coefficient of 0.960 (P < 0.01). The mean oral fluid-to-serum concentration ratio was 0.99 (95% confidence interval [CI], 0.88 to 1.10) with Bland-Altman analysis. In conclusion, an oral fluid method of analysis was successfully developed and clinically validated for fluconazole in pediatric patients and can be a noninvasive, painless alternative to perform TDM of fluconazole when blood sampling is not possible or desirable. When patients receive prolonged courses of antifungal treatment and use fluconazole at home, this method of analysis can extend the possibilities of TDM for patients at home.